Late Epigravettian and Mesolithic foragers of the eastern Alpine region: Animal exploitation and ornamental strategies at Riparo Biarzo (Northern Italy). (22nd November 2016) - Bertolini, Marco; Cristiani, Emanuela; Modolo, Marta; Visentini, Paola; Romandini, Matteo
Abstract: The eastern Alpine region of Italy represents a well-known area with regards to the study of Late Pleistocene and Early Holocene forager adaptations in the whole peninsula. Caves, shelters and open-air sites, which are numerous in this region, have yielded traces of human re-peopling from mountaineous environments since the Late Glacial and until the Early Holocene. However, the archaeological record of the region lacks evidence about long lasting forager occupations. Exceptionally for the eastern Alpine sector, Riparo Biarzo (Natisone Valley, Julian Prealps) has yielded important evidence of continuous forager frequentation from Late Pleistocene to Early Holocene. The authors discuss the results of the analyses of animal remains and shell ornaments recovered in the Late Epigravettian and Mesolithic units of the site and their significance for understanding continuity and changes in the subsistence and symbolic strategies during these periods in the region. Archaeological data indicate an abundance of wild boar remains during both the Late Pleistocene and the Early Holocene at Biarzo, which makes hunting strategies at this site unique with regards to other contemporary contexts of the eastern Alpine region. Also, modalities of selection, production and use of ornaments in the same periods reveal the existence of established exchange networks, mobility strategies and connectivity between the eastern Alpine and the North Adriatic regions during the Late Epigravettian and throughout the Mesolithic.